Analysis of Black Mura Caused by Photo Ioff. (17th July 2020) - Li, Zongxiang; Liu, Yao; Yun, Xiangnan; Wang, Baoqiang; Li, Liangliang; Feng, Yuchun; Liu, Zheng; Chen, Xi; Wu, Hongjiang
Abstract : The researched Black Mura partly occurred in TFT‐LCD which is caused by the bigger photo Ioff in this area. Direct evidence is given through a theoretical calculation method, by which brightness difference between Black Mura area and normal area can be got, it is corresponding by contrast with the actual data and influenced by storage capacitance and ΔIoff through a fitting formula. Besides, the difference between Active First and Pre‐ashing is given which is the root cause in this case.